Competition Ethics and the Dynamics of Customer Behavior in Forming Banking Financing Portfolios - Rina El Maza; Anindya; Nazeri (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the influence of competitive ethics and customer behavior dynamics on the formation of bank financing portfolios, with loan tenor, customer intertemporal preferences, and subjective benefits serving as mediating variables. The study is motivated by the increasing need for ethical competition and a deeper understanding of customer financial behavior to improve the sustainability and effectiveness of banking financing strategies. Design/methodology/approach – This study employs a quantitative approach with a causal research design. Data were collected through a questionnaire survey administered to banking financing customers and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both the direct and indirect relationships among the proposed constructs. Findings/Results – The findings reveal that competitive ethics significantly influence customer behavior dynamics, particularly in shaping loan tenor decisions and intertemporal preferences. Furthermore, loan tenor and intertemporal preferences positively and significantly affect customers' subjective benefits, which subsequently contribute to the development of bank financing portfolios. Mediation analysis confirms that subjective benefits play a significant mediating role in the relationship between customer behavior dynamics and bank financing portfolios. Originality/Value – This study extends the literature on competitive ethics and customer financial behavior by integrating subjective benefits as a key explanatory mechanism in the formation of bank financing portfolios. The findings provide practical insights for banking institutions to strengthen ethical competition strategies, enhance financing risk management, and develop customer-oriented financing products that align with customers' preferences and perceived benefits.